The Effect of Balcony to Enhance the Natural Ventilation of Terrace Houses in the Tropical Climate of Malaysia - Nurakmal, Abdullah@ Goh Tuo Ho; Mazlan, Mohd Tahir; Usman, Iliyasu; Mohammadi, A.R.; Utaberta, Nangkula; Che Ani, A. I. (2010)
Utilizing natural ventilation is one of the parameter to achieving a sustainable building. Natural ventilation in terrace houses is of primary importance especially in a tropical country with hot and humid climate like Malaysia. Apart from the use of window and door opening, a balcony is an alternative architectural element as a wind scoop for scooping the air into a building to allow for better ventilation in naturally ventilated buildings. In this study, double store terrace house is selected in Kuala Lumpur. The aim of the study to analyze the effect of balcony to enhance natural ventilation and also, proved that the balcony could be used as transitional space to control and induce the outdoor air flow into indoor spaces of terrace house. This analysis used IES <Virtual Environment > 6.0, MacroFlo simulation method which measured Volume flow, temperature, humidity, natural vent gain of the terrace house model. Unlike previous studies, the finding indicates that using the balcony in terrace houses in warm and humid climate like Malaysia cannot be workable to increase the natural ventilation. discussion and recommendations are made regarding future researches in this area.